The Righteous Among the Nations of the World: An Exploration of Free-Choice Learning - Yelich Biniecki, Susan; Donley, S. (My University, 2016)
The purpose of this study was to explore how learners make meaning of their experiences at exhibits depicting narratives of the Polish Righteous Among the Nations of the World, free-choice learning contexts. The study focused on two exhibits at a university in the mid-Western United States. The conceptual framework of the study integrates free-choice learning, the role of narratives, reflection, and Holocaust education. Three main mechanisms emerged from the qualitative analysis and interpretation of data of how participants made meaning of their experiences: through emotions, being challenged, and broadening awareness. This study further informs our understanding of meaning making and learning in free-choice learning contexts, suggesting ways in which we might provide additional prompts to bridge historical distance and integrate connectors to learners’ personal contexts in international education exhibits. © 2016, © The Author(s) 2016.
Citation: Yelich Biniecki, S. M., & Donley, S. (2016). The Righteous Among the Nations of the World: An Exploration of Free-Choice Learning. SAGE Open, 6(3). doi:10.1177/2158244016659319
Keywords: Free-Choice Learning; Holocaust Education; International Education; Narratives; Poland; Righteous Among The Nations Of The World